Perilaku Prokrastinasi Akademik dan Penanganannya dengan Teknik Solution Focused Brief Counseling - Bimo Tangke Padang; Salmi Silambi; Sance Syakema (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
One of the most common problems faced by students is academic procrastination. This issue often leads to increased stress, poor academic performance, and difficulties in self-control. This study aims to examine academic procrastination behavior and evaluate the Solution Focused Brief Counseling (SFBC) approach as an alternative intervention. The research was conducted using a qualitative approach in the form of a literature study. Data were obtained from various relevant scientific sources, including national and international journals, reference books, and previous research findings published within the last ten years. The data were analyzed using a content analysis technique by organizing the information into several main themes, including the factors causing academic procrastination, its impact on students, and the effectiveness of SFBC implementation. The findings indicate that academic procrastination is influenced by internal factors, such as low learning motivation, weak self-control, and poor time management skills. External factors also include an unconducive learning environment and a lack of social support. In addition, the results show that the SFBC technique helps students reduce task-delay behavior by setting clear goals, strengthening self-potential, and developing realistic solution plans. Therefore, SFBC can be considered a relevant and effective approach in guidance and counseling services to address academic procrastination.